2
$\begingroup$

$$\lim_{x \to 0} \dfrac{2\sqrt{x+1}-x-2}{x^2}$$

I can solve it using l'Hôpital but just cannot find a way to do it algebraically.

$\endgroup$
6
  • 2
    $\begingroup$ What limit are you trying to find? $\endgroup$ Feb 18, 2013 at 21:19
  • $\begingroup$ Limit as $x$ goes to what? $\endgroup$
    – Jim
    Feb 18, 2013 at 21:19
  • $\begingroup$ @user62872 No limit, no question. It's an easy downvote. But I'll refrain from doing that to give you time to properly ask the question. $\endgroup$
    – Git Gud
    Feb 18, 2013 at 21:20
  • $\begingroup$ I am sorry limit as x approaches 0, couldnt find how to edit the original post $\endgroup$
    – user62872
    Feb 18, 2013 at 21:20
  • 2
    $\begingroup$ @user62872 No problem. Don't forget to upvote answers which you find helpful and accept your favorite one. $\endgroup$
    – Git Gud
    Feb 18, 2013 at 21:24

4 Answers 4

5
$\begingroup$

$$\begin{align} \lim_{x\to 0}\frac{2\sqrt{x+1}-x-2}{x^2} &= \lim_{x\to 0}\frac{2\sqrt{x+1}-(x+2)}{x^2} \frac{2\sqrt{x+1}+(x+2)}{2\sqrt{x+1}+x+2}\\ &= \lim_{x\to 0}\frac{4(x+1)-(x+2)^2}{x^2} \frac{1}{2\sqrt{x+1}+x+2}\\ &= \lim_{x\to 0}\frac{4(x+1)-(x^2+4x+4)}{x^2} \frac{1}{2\sqrt{x+1}+x+2}\\ &= \lim_{x\to 0}\frac{-x^2}{x^2}\frac{1}{2\sqrt{x+1}+x+2}\\ &=\lim_{x\to 0}\frac{-1}{2\sqrt{x+1}+x+2}\\ &=-\frac{1}{4} \end{align}$$

$\endgroup$
2
  • $\begingroup$ There's a typo in the last $\lim$. Nice answer. $\endgroup$
    – Git Gud
    Feb 18, 2013 at 21:35
  • 3
    $\begingroup$ I believe you left out a negative somewhere, nice work though $\endgroup$
    – user62872
    Feb 18, 2013 at 21:36
3
$\begingroup$

Multiply the top and bottom by $2\sqrt{x + 1} + x + 2$.

$\endgroup$
3
$\begingroup$

$$\lim_{x \to 0} \dfrac{2\sqrt{x+1}-x-2}{x^2} = \lim_{x\to 0} \dfrac{2\sqrt{x+1} - (x + 2)}{x^2}$$

To start, multiply numerator and denominator by the conjugate $$2\sqrt{x + 1} + (x + 2)$$

$\endgroup$
2
  • $\begingroup$ Thank you, I had a dumb parentheses mistake $\endgroup$
    – user62872
    Feb 18, 2013 at 21:37
  • $\begingroup$ You're welcome, user62872! $\endgroup$
    – amWhy
    Feb 18, 2013 at 21:53
1
$\begingroup$

We have $\sqrt{1+x}=1+\frac{1}{2}x+(\frac{1}{2})(\frac{-1}{2})\frac{x^2}{2}+o(x^2)$, so $$\lim_{x \to 0} \dfrac{2\sqrt{x+1}-x-2}{x^2}=\lim_{x \to 0}\dfrac{-\frac{1}{4}x^2+o(x^2)}{x^2}=-\frac{1}{4}$$

$\endgroup$

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .